Speed of Action of Trichlopic Herbicide with Mixture of Solar Oil and Water Mixture for Controlling Rubber Trees at Arboretum Samarinda Training Center for LHK - Jinarto, Sugeng (Universitas 17 Agustus 1945 Samarinda, 2018)
In the Samarinda BDLHK Arboretum there is an increasing number of competing rubber species that become competitors against collection plants. Triklopir herbicide is a systemic herbicide that is selective to control broadleaf herbs. The study was conducted on January 17, 2018 until February 21, 2018, while the location of the study was carried out at the Arboretum of the Samarinda LHK Training Center, using materials and equipment such as: Herbicides with trichloride butoxy active ethyl ester: 480 g / l (equivalent to trichloprate: 345 g / l), diesel fuel, water, brushes, buckets, machetes and masks. The trees targeted for poisoning are types of rubber (Hevea brasiliensis). The results showed that the mixture of trichlopir herbicide and diesel fuel fuel reacted faster and statistical tests using randomized block design obtained significant differences in the effect of treatment. For a short time and costs a little more expensive is recommended with a mixture of trichlopric herbicides and diesel fuel, whereas if without a fast and inexpensive time target in terms of cost, the recommended mixture is trichlopric herbicide and water.